Electronic identification key and data base to the genus Chinavia (Heteroptera: Pentatomidae) with morphological and distributional data - Servino, Leonardo Matheus; Schwertner, Cristiano Feldens (Zootaxa, 2020)
The genus Chinavia Orian has a great diversity of species, being distributed in the Nearctic, Neotropical and Afrotropical regions (Rolston 1983; Schwertner & Grazia 2007, Grazia & Schwertner 2017). The genus is included in the subfamily Pentatominae, tribe Nezarini, whose individuals retain their green coloration after death, average size between 9 and 19 mm, and considered polyphagous (Rolston 1983; Schwertner et al. 2002; Rider 2020). Some species of Chinavia are recorded as important crop pests in different countries (e.g. Matesco et al. 2007; Herbert & Toews 2012), and those species are better known regarding distribution, ecology and other biological aspects. However, the great majority of species is known only for the adult morphology, and there are still problems concerning the correct identification of the species due to their wide distribution.